Chemokine (C‐C motif) receptor 7 (CCR7) associates with the tumour immune microenvironment but not progression in invasive breast carcinoma. (30th March 2017) - Sonbul, Sultan N; Gorringe, Kylie L; Aleskandarany, Mohammed A; Mukherjee, Abhik; Green, Andrew R; Ellis, Ian O; Rakha, Emad A
Abstract: Some previous studies have reported that the chemokine (C‐C motif) receptor 7 (CCR7) plays a role in breast cancer, is associated with lymph node metastasis and drives the site of distant metastasis. However, the impact of its expression on patient outcome and its association with tumour infiltrating inflammatory cells remain to be validated. We evaluated CCR7 protein expression by immunohistochemistry in a large well characterized cohort ( n  = 866) of early invasive primary breast cancers. CCR7 was expressed in the cytoplasm and membrane of tumour cells. We observed a weak positive association of high CCR7 expression when in either cellular component, but not both together, with axillary lymph node stage 3 tumours ( p  = 0.043). Logistic regression analysis of lymph node stage revealed no independent predictive value for CCR7 expression. CCR7 expression was higher in HER2 positive tumours ( p  = 0.03) and associated with positive CD68+ FOXP3+ tumour infiltrating cells. CCR7 staining was negatively associated with CD3+ cells. There was no significant association of CCR7 expression with breast cancer recurrence or survival. We conclude that while CCR7 is not a useful biomarker for predicting lymph node metastasis, it may reflect altered intra‐ and inter‐cellular signalling related to the immune microenvironment. The subcellular localization of CCR7 appears to affect the nature of these interactions.